1997
DOI: 10.1021/jp9618136
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conductance and Viscosity of Concentrated H2SO4/H2O Binary Systems at Low Temperatures:  Correlation with Phase Transitions

Abstract: Density, viscosity, and electrical conductance of concentrated H 2 SO 4 /H 2 O systems (above 66 wt % H 2 SO 4) were measured in the subambient temperature region. The lowest temperature of measurement was 198 K. Density varied linearly with temperature. Viscosity and conductance data were fitted to the Vogel-Tammann-Fulcher (VTF) equation and also to the power-law equation, the latter being a better functional form to describe the temperature dependence of transport properties. Concentration dependences of vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 40 publications
(75 reference statements)
2
21
0
Order By: Relevance
“…B2) suggest that the particles observed under dry conditions consisted of oxalic acid dihydrate or non-stoichiometric hydrates containing about two water molecules per oxalic acid molecule. This is consistent with earlier studies suggesting that the tendency of aqueous acids to form glasses is most pronounced at compositions that correspond to stable hydrates (e.g., amorphous sulfuric acid monohydrate; Kanno and Itoi, 1984;Das et al, 1997;Tomikawa and Kanno, 1998;Koop, 2004). Besides hydration also dimer formation and surface kinetic effects could possibly play a role in making OA particles less volatile than glutaric acid particles (surface vs. bulk accommodation, adsorption & desorption rate coefficients, etc.…”
Section: Particle Composition and Stabilitysupporting
confidence: 91%
“…B2) suggest that the particles observed under dry conditions consisted of oxalic acid dihydrate or non-stoichiometric hydrates containing about two water molecules per oxalic acid molecule. This is consistent with earlier studies suggesting that the tendency of aqueous acids to form glasses is most pronounced at compositions that correspond to stable hydrates (e.g., amorphous sulfuric acid monohydrate; Kanno and Itoi, 1984;Das et al, 1997;Tomikawa and Kanno, 1998;Koop, 2004). Besides hydration also dimer formation and surface kinetic effects could possibly play a role in making OA particles less volatile than glutaric acid particles (surface vs. bulk accommodation, adsorption & desorption rate coefficients, etc.…”
Section: Particle Composition and Stabilitysupporting
confidence: 91%
“…B2) suggest that the particles observed under dry conditions consisted of oxalic acid dihydrate or non-stoichiometric hydrates containing about two water molecules per oxalic acid molecule. This is consistent with earlier studies suggesting that the tendency of aqueous acids to form glasses is most pronounced at compositions that correspond to stable hydrates (e.g., amorphous sulfuric acid monohydrate; Kanno and Itoi, 1984;Das et al, 1997;Tomikawa and Kanno, 1998;Koop, 2004). Besides hydration also dimer formation and surface kinetic effects could possibly play a role in making OA particles less volatile than glutaric acid particles (surface vs. bulk accommodation, adsorption & desorption rate coefficients, etc.…”
Section: Particle Composition and Stabilitysupporting
confidence: 91%
“…For a given composition, the computed value is expected to be very close to since it represents the ideal glass transition temperature which should be independent of the transport property. 162 Das et al 107 found that the values of and are in fact close to one another over the explored concentration range Their investigations have also highlighted correlations between the viscosityconcentration curves and the phase diagram of the system.…”
Section: (Ii) Power-law Equations For Viscosity and Electrical Conducmentioning
confidence: 90%
“…Concerning the system studied in the subambient region, between 200 and 300 K, Das et al 107 have found that a power-law type equation [158][159][160] based on the mode coupling theory of relaxation in supercooled liquids 161 is better than a Vogel-Tammann-Fulcher type equation 108 to describe the temperature dependence of the electrical conductivity and the viscosity .…”
Section: (Ii) Power-law Equations For Viscosity and Electrical Conducmentioning
confidence: 99%